1997
DOI: 10.1161/01.cir.96.10.3360
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Analysis of Proliferative Activity in Carotid Endarterectomy Specimens by Immunocytochemical Detection of the Cell Cycle–Related Antigen Ki-67

Abstract: Our results suggest that proliferation in advanced human carotid lesions is confined to the intima and focally concentrated in central plaque regions negative for alpha-actin. Furthermore, it apparently occurs primarily as part of inflammatory processes and structural repair predominantly involving macrophages, as well as unspecific mesenchymal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 39 publications
1
43
1
1
Order By: Relevance
“…In contrast, the saturated acyl species are inactive in eliciting vascular wall remodeling [43,55]. Using atherosclerotic tissue specimens from patients who underwent operations for high-grade carotid stenosis, we analyzed the LPA content and composition of the lipid-rich core that is characterized histologically by extracellular lipid deposits and beds of foam cells [80]. This region had the highest LPA content [77,81].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the saturated acyl species are inactive in eliciting vascular wall remodeling [43,55]. Using atherosclerotic tissue specimens from patients who underwent operations for high-grade carotid stenosis, we analyzed the LPA content and composition of the lipid-rich core that is characterized histologically by extracellular lipid deposits and beds of foam cells [80]. This region had the highest LPA content [77,81].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of data on DNA synthesis in human atherosclerosis are confined to advanced lesions only. They show low levels of DNA synthesis (0% to 2%), [15][16][17][18] but this level is significantly higher than in the nondiseased arterial wall. 14,15,18,19 One study on DNA synthesis in early fatty-streak lesions also reports low values of DNA synthesis (0% to 2%).…”
Section: Discussionmentioning
confidence: 99%
“…They show low levels of DNA synthesis (0% to 2%), [15][16][17][18] but this level is significantly higher than in the nondiseased arterial wall. 14,15,18,19 One study on DNA synthesis in early fatty-streak lesions also reports low values of DNA synthesis (0% to 2%). 20 DNA synthesis in these human lesions is confined primarily to either the macrophage-derived foam cell 15,17,18 or the VSMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be argued that apoptotic death of any cell type in the plaque may favour plaque regression over plaque progression. However, the rate of apoptotic cell death in the plaque (2 ± 10%) (Bauriedel et al, 1998;Kockx et al, 1996;Mallat et al, 1997) may, in many instances, exceed the reported rate of cell proliferation (51%) (Brandl et al, 1997;Gordon et al, 1990). In the light of observations that human atherosclerotic plaques are generally more prone to progression rather than regression, it can be suggested that apoptosis is actually implicated in natural plaque progression (rather than regresssion), through development of the acellular lipid necrotic' core.…”
Section: Apoptosis In the Vasculaturementioning
confidence: 97%